Włocławska Fabryka Sulfit-Celulozy I. & M. Cassirer w latach 1898–1920 - Dziki, Tomasz (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2015)
In 1898, the two German entrepreneurs of the Jewish descent, Max and Izydor Cassirer, founded a company the aim of which was to build a sulfate cellulose factory in Wloclawek. Within the same year they purchased first properties and started the building process that was completed in 1899. From the very beginning the factory in Wloclawek was considered to be the greatest manufacturing enterprise in town, was the only cellulose factory in Kingdom of Poland (until 1914), and one of a few in the whole Russian Empire. The opening of the factory had an impact on the demographic and spatial development of the town and forced changes in the branch structure of the Wloclawek industry. One of the outcomes of the manufacturing of the raw matrial that is central to paper production was opening of the two paper mills in Wloclawek. The establishment of the cellulose factory had also social effects in that it grounded the image of the town as the labour centre. The local society faced then for the fist time with environmental pollution caused by the factory on such a large scale. The company remained in the German hands until the restoration of Poland’s sovereignty, then, in 1920, it was sold, and eventually joined a well-known Polish pulp and paper concern.